The Role and Place of Parents of Children with Disabilities in Inclusive Education in Serbia - Lazarevic, Emilija; Kopas-Vukašinović, Emina (International Journal about Parents in Education, 2023)
The current Law on the fundamentals of the education system adopted in 2009 states that inclusive education is a legal obligation in Serbia, which has resulted in the increased accessibility of education for children with disabilities in regular schools. Numerous challenges have been encountered in the implementation of inclusive education in our country, while the role and place of parents of children with disabilities in inclusive education has remained very important. In spite of the changes implemented so far, solutions for enabling support, procedures and mechanisms for the accomplishment and development of partner relations between teachers and parents in inclusive education have not yet been sufficiently developed in our education system. Parents of children with disabilities in our country are rarely partners in the process of education in which their children are involved. This paper discusses the role and place of parents of children with disabilities from the standpoint of the current situation in inclusive education by reviewing the results and reports of current studies in our country.